2000
DOI: 10.1007/s004210050677
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic studies of human soleus and gastrocnemius muscle architecture: gender variability

Abstract: The purpose of this study was to establish if there are gender differences in muscle architecture in relaxed human soleus and gastrocnemius muscles of normal, live subjects. Ultrasonography was used to measure fiber bundle length, muscle thickness, and angles of pennation in a total of ten predetermined sites in the medial and lateral heads of gastrocnemius and the anterior and posterior soleus in 19 males and 16 females. Percentage differences between males and females for each parameter were recorded. Gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
156
4
8

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(182 citation statements)
references
References 39 publications
13
156
4
8
Order By: Relevance
“…Figure 5d shows that the fibers of the soleus muscle have a complicated architecture and change directions along the SI direction. US and morphologic measurements of the soleus indicate that it is compartmentalized into a unipennate posterior group and a bipennate anterior group (22,26). Furthermore, three-dimensional structure and velocity maps from MRI have shown that the anterior soleus fibers are arranged radially around the median septum (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5d shows that the fibers of the soleus muscle have a complicated architecture and change directions along the SI direction. US and morphologic measurements of the soleus indicate that it is compartmentalized into a unipennate posterior group and a bipennate anterior group (22,26). Furthermore, three-dimensional structure and velocity maps from MRI have shown that the anterior soleus fibers are arranged radially around the median septum (27).…”
Section: Discussionmentioning
confidence: 99%
“…B-mode US is a noninvasive imaging modality that has been widely used to image muscle architecture (26,29,30). It is fast and allows real-time measurements of fiber lengths and pennation angles to be made even during isometric contraction (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…A Toshiba SSH-140A real time ultrasound scanner with 5 MHz or 7n5 MHz linear array transducer was used for the study (Leekam et al 1999 ;Chow et al 2000). Information was processed with the Agfa Impax System (Pax System).…”
Section: Ultrasonographic Studymentioning
confidence: 99%
“…Recently, it was shown that the problem of electrode alignment can be overcome with principal component analysis (PCA), which was applied on multiple monopolar EMG channels and is thus unbiased with respect to the muscle fiber direction (Staudenmann et al, 2006). So far, PCA-processed monopolar multi-channel EMG has been applied on the triceps brachii, and triceps surae (Staudenmann et al, 2006(Staudenmann et al, , 2009a, both mainly pennate and architecturally complex muscles (Chow et al, 2000;Kawakami et al, 1993). A substantial improvement in muscle activation estimates was achieved with PCA as compared to multiple bipolar EMG using the same electrodes (Staudenmann et al, 2006(Staudenmann et al, , 2009a, suggesting that the misalignment of (multiple) bipolar EMG is a cause of errors in the estimation.…”
Section: Introductionmentioning
confidence: 99%